Safety and efficacy of the selective sphingosine 1-phosphate receptor modulator ozanimod in relapsing multiple sclerosis (RADIANCE): a randomised, placebo-controlled, phase 2 trial. Issue 4 (April 2016) - Cohen, Jeffrey A; Arnold, Douglas L; Comi, Giancarlo; Bar-Or, Amit; Gujrathi, Sheila; Hartung, Jeffrey P; Cravets, Matt; Olson, Allan; Frohna, Paul A; Selmaj, Krzysztof W; ,
Summary: Background: Modulation of sphingosine 1-phosphate (S1P) receptors in a non-selective manner decreases disease activity in patients with multiple sclerosis but has potential safety concerns. We assessed the safety and efficacy of the oral selective S1P receptor modulator ozanimod in patients with relapsing multiple sclerosis. Methods: RADIANCE is a combined phase 2/3 trial. Patients with relapsing multiple sclerosis were recruited from 55 academic and private multiple sclerosis clinics in 13 countries across Europe and the USA. Eligible participants were aged 18–55 years, had an Expanded Disability Status Scale (EDSS) score of 0–5·0, and had either one or more relapses in the previous 12 months, or one or more relapses in the past 24 months and one or more gadolinium-enhancing lesions on MRI in the previous 12 months before screening. Participants were assigned by a computer-generated randomisation sequence in a 1:1:1 ratio to ozanimod (0·5 mg or 1 mg) or matching placebo once daily for 24 weeks by an independent, unmasked, statistical team. Trial participants, study site personnel, MRI assessors, steering committee members, and the study statistician were masked to treatment assignment. To attenuate first-dose cardiac effects, ozanimod was up-titrated from 0·25 mg to 0·5 mg or 1 mg over 8 days. The primary endpoint was the cumulative number of total gadolinium-enhancing MRI lesions measured by an independent MRI analysis centre at weeks 12–24 after treatment initiation. Analysis was by intention to treat. Here, we report results from the 24-week phase 2 trial. This trial is registered withClinicalTrials.gov, numberNCT01628393 . The 2-year phase 3 trial is ongoing. Findings: The first patient was randomised on Oct 18, 2012, and the final visit of the last randomised patient was on May 11, 2014. The intention-to-treat and safety population consisted of 258 participants, 88 were assigned placebo, 87 ozanimod 0·5 mg, and 83 ozanimod 1 mg; 252 (98%) patients completed the assigned treatment. The mean cumulative number of gadolinium-enhancing lesions at weeks 12–24 was 11·1 (SD 29·9) with placebo compared with 1·5 (3·7) with ozanimod 0·5 mg (odds ratio 0·16, 95% CI 0·08–0·30; p<0·0001) and 1·5 (3·4) with ozanimod 1 mg (odds ratio 0·11, 95% CI 0·06–0·21; p<0·0001). Three serious adverse events unrelated to treatment were reported in patients assigned ozanimod 0·5 mg: optic neuritis, somatoform autonomic dysfunction, and cervical squamous metaplasia (HPV-related). No serious infectious or cardiac adverse events were reported, and no cases of macular oedema arose. The most common adverse events in the ozanimod 0·5 mg and 1 mg groups compared with placebo were nasopharyngitis (11 and five vs 12), headache (five and three vs eight), and urinary-tract infections (six and two vs two). The maximum reduction in mean heart rate by Holter monitoring during the first 6 h in ozanimod-treated participants was less than 2 beats per min (bpm) compared with baseline, with no patient having a minimum hourly heart rate less than 45 bpm. Electrocardiograms and 24-h Holter monitoring showed no increased incidence of atrioventricular block or sinus pause with ozanimod. Interpretation: Ozanimod significantly reduced MRI lesion activity in participants with relapsing multiple sclerosis, with a favourable safety profile over a period of 24 weeks. These findings warrant phase 3 trials, which are ongoing. Funding: Receptos, Inc.